Dual-Carbon Assisted Oxygen Vacancy Engineering for Optimizing Mn(III) Sites to Enhance Zn-air Battery Performances - Zhou, Benji; Xu, Nengneng; Lu, Tuo; Wang, Yongxia; Lou, Shuaifeng; Cai, Dongqing; Wu, Liangcai; Yang, Woochul; Liu, Guicheng; Lee, Joong Kee; Qiao, Jinli (John Wiley & Sons Ltd., 2025)
Owing to kinetic-sluggish nature of electrocatalytic oxygen transformation processes, it is pivotal to develop durable and efficient bifunctional air electrode catalysts for fabricating high-performance Zn–air batteries (ZABs). In this work, oxygen vacancy (Ov) induced Mn(III) sites optimization is achieved via nano-micro structure modulation. Protonated carbon nitride (p-C3N4) is applied as a structure-stiffening module to immobilize α-MnO2 on N/P-doped active carbon (NPAC) and induce Ov construction. X-ray adsorption spectra (XAS) disclose the formation of Ov and Mn(III) sites in MCC, the unit coordination structure is well maintained with the aid of a dual-carbon strategy. Mn(III) sites efficiently catalyze oxygen reduction/evolution reaction (ORR/OER), MCC shows high half-wave potential (E1/2) of 0.88 V for ORR and low potential at 10 mA cm−2 (Ej = 10) of 1.64 V for OER. According to density functional theory (DFT) simulations analysis, the gorgeous bifunctional activity is owing to that optimized charge distribution facilitates the intermediates transformation. Aqueous ZABs based on MCC manifests high peak power density of 452 mW cm−2 and durable cycling stability of 1640 h. Quasi-solid-state ZABs based on MCC also show satisfactory performances (175 mW cm−2, 105 h). This work provides the route to develop efficient and durable electrocatalyst for constructing ZABs with long lifespan and high-power-density.